Kajian tentang Nilai-nilai Inti Budaya Organisasi dan Komitmen Anggota Aiesec Local Committee Universitas Brawijaya Malang - Al Amin, Raden Pamungkas; Noermijati (Jurnal Aplikasi Manajemen, 2010)
Organizational culture core values is the important thing for the organization members. The aim of this research is for knowing the simultaneously and partially effect of the organizational culture core values on the commitment of AIESEC Local Committee University of Brawijaya members. The population is the entire members of AIESEC Local Committee University of Brawijaya. Involving 65 members as sample, by using multiple regression analysis method. The result of the research shows that the variables for organizational core value: include activating leadership,demonstrating integrity, living diversity, enjoying participation, striving for excellence, acting sustainably, simultaneously affected the members commitment. Partially, striving for excellence and enjoying participation affected members’ commitment, while activating leadership, demonstrating integrity, living diversity, acting sustainably, did not affect members’ commitment. The striving for excellence is dominant in affecting members commitment. Therefor, educating every member on organizational culture core values should be done continuously, so that a good understanding about the core value can be achieved. Finally, members commitment can be increased.